Acid-resistant photovoltaic adhesive film for N-type battery and preparation method of acid-resistant photovoltaic adhesive film
Through the blending and surface coating grafting technology of silane-modified nanomaterials with carbodiimide anti-hydrolyzers and ion trapping agents, the problem of insufficient free acid trapping ability in new N batteries is solved, and the acid-resistant photovoltaic glue is improved The corrosion resistance and light transmission properties of the film extend the service life of the battery module.
Patent Information
- Application Number
- CN202411214039.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-31
- Publication Date
- 2024-12-17
AI Technical Summary
The EVA resin of the new N-cell is prone to hydrolysis during hydrothermal aging to produce free acetic acid, resulting in corrosion of the surface gate lines of the battery cell. The existing solid alkali nanomaterials are insufficient to capture performance and cannot resist corrosion for a long time.
Silane-modified nanomaterials are blended with carbodiimide-based anti-hydrolyzing agents and ion capture agents, and the alkalinity and capture ability of the nanomaterials are improved through surface coating grafting technology to form an acid-resistant photovoltaic film.
It effectively improves the corrosion resistance of the adhesive film, reduces yellowing, improves light transmission and water resistance, and extends the service life of the battery module.
Smart Images

Figure CN119144245A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and specifically relates to a film or sheet-shaped adhesive, and in particular to an acid-resistant photovoltaic adhesive film for N-type batteries and a preparation method thereof. Background Art
[0002] In recent years, with the upgrade of photovoltaic cells, photovoltaic N-type modules and double-glass modules have gradually become the mainstream of the market. Against this background, the demand for adhesive films will also show a steady growth trend. Due to the special characteristics of the slurry, the new N-type battery has worse acid resistance than the traditional P-type battery.
[0003] Due to the property that the vinyl acetate side chains of EVA resin are easily hydrolyzed to produce free acetic acid during the hydrothermal aging process, and react with the grid lines on the surface of the battery cell under high temperature and water vapor conditions, causing corrosion of the grid lines, thereby causing the power of the components to drop, which greatly limits the application of EVA photovoltaic film.
[0004] In response to the corrosion problem of battery cells, some companies currently generally adopt the solution of introducing solid alkaline nanomaterials to partially neutralize the free acetic acid produced by EVA aging and hydrolysis, thereby delaying the corrosion of the battery grid lines. However, the alkalinity and capture performance of pure inorganic nanomaterials are insufficient, and they cannot capture the free acetic acid in the component system in time. In addition, the amount added is small, and with the continuous infiltration of water vapor during the long-term aging process, they gradually become ineffective and cannot play a long-term anti-corrosion role.
[0005] Therefore, how to overcome the problem of insufficient capture ability of alkaline nanomaterials for free acids is a technical problem that urgently needs to be solved in this field.
[0006] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention
[0007] The embodiments of the present disclosure at least provide an acid-resistant photovoltaic adhesive film for an N-type battery and a preparation method thereof.
[0008] In a first aspect, an embodiment of the present disclosure provides a method for preparing an acid-resistant photovoltaic adhesive film for an N-type battery, comprising the following steps: step S1, preparing a silane-modified nanomaterial, namely weighing nano-oxide, acetone, alkaline silane and acetic acid solution, heating and stirring for reaction grafting, and then centrifuging and heating and drying to obtain the silane-modified nanomaterial; step S2, blending the silane-modified nanomaterial with an ion capture agent, a carbodiimide anti-hydrolysis agent and an EVA resin in proportion, heating and extruding, and pelletizing after cooling to obtain a super acid-resistant masterbatch; step S3, mixing the super acid-resistant masterbatch and the EVA resin in proportion, adding an auxiliary agent, and then casting, embossing, cooling and winding in a screw extruder to obtain an acid-resistant photovoltaic adhesive film for an N-type battery.
[0009] In an optional embodiment, the step S1 specifically includes the following components in parts by weight: 5-10 parts of nano-oxide; 10-30 parts of acetone; 0.1-2 parts of alkaline silane; 0.1-0.5 parts of acetic acid; wherein the pH of the acetic acid is 3.
[0010] In an optional embodiment, the step S1 is heating and stirring the reaction, followed by centrifugation and heating and drying to obtain the silane-modified nanomaterial. Specifically, the reaction is heated to 50°C and stirred for 3-5h, followed by centrifugation at 8000-12000r / min and then heated to 103°C to dry to obtain the silane-modified nanomaterial.
[0011] In an optional embodiment, the nano-oxide includes any one or more combinations of magnesium oxide, aluminum hydroxide, calcium hydroxide, zirconium oxide, aluminum oxide, zinc oxide, zinc acetate, aluminum hydroxide, zinc hydroxide, hydrotalcite, zeolite, molecular sieve, calcium lactate, zinc lactate and barium oxide.
[0012] In an optional embodiment, the basic silane includes 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminoethylaminopropyltrimethoxysilane, 3-(phenylamino)propyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylbis(trimethylsiloxy)methylsilane, N-(n-butyl)-r-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropyl A combination of any one or more of propyltrimethoxysilane, N-β-aminoethyl-γ-aminopropyltriethoxysilane, N-cyclohexyl-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, di(3-trimethoxysilylpropyl)amine, diethylenetriaminopropyltrimethoxysilane, monoaminosilane oligomer, bisaminosilane oligomer and N-n-butyl-3-aminopropyltrimethoxysilane.
[0013] In an optional embodiment, the ion capture agent includes any one or more combinations of anionic polyacrylamide, 18-crown ether-6 and polyether silane.
[0014] In an optional embodiment, the carbodiimide anti-hydrolysis agent includes any one or more combinations of monomeric carbodiimide, polycarbodiimide and its derivative N,N'-dicyclohexylcarbodiimide.
[0015] In an optional embodiment, the step S2 specifically includes the following components in parts by weight: 80-96 parts of EVA resin; 2-10 parts of silane-modified nanomaterials; 1-5 parts of carbodiimide anti-hydrolysis agents; and 1-5 parts of ion capture agents.
[0016] In an optional embodiment, the auxiliary agent in step S3 includes an initiator, a co-crosslinking agent, a light stabilizer, an antioxidant and a silane coupling agent.
[0017] In a second aspect, the embodiments of the present disclosure further provide an acid-resistant photovoltaic adhesive film for an N-type battery, which is prepared by the method described above.
[0018] The beneficial effects of the present invention are that the acid-resistant photovoltaic adhesive film for N-type batteries and the preparation method thereof have the following advantages:
[0019] 1. Use surface coating grafting technology on existing nanomaterials and introduce alkaline aminosilane coupling agents to improve the solid alkalinity of nanomaterials, effectively improve the free acid capture ability, and increase the corrosion resistance of the film. At the same time, the surface free energy of the surface coating or powder is reduced, and the dispersion is better after granulation, which reduces the haze increase caused by the introduction of nanomaterials and increases the light transmittance of the film;
[0020] 2. Conventional amino compounds introduced into EVA photovoltaic adhesive film are prone to yellowing, but by combining nanomaterials with aminosilane grafting, the nanomaterials can timely absorb the colored groups produced by the decomposition of amino groups, thereby improving the acid resistance of the film and reducing the yellowing of the film;
[0021] 3. Introduce organic ion capture agents and carbodiimide anti-hydrolysis agents into the masterbatch in proportion, increase the film's ability to capture positively charged Na / K ions on the basis of the original anti-acid additives, and further reduce the accumulation of free acetic acid and positively charged Na / K ions on the surface of the battery cell. At the same time, the carbodiimide anti-hydrolysis agent can react with functional groups such as carboxyl and hydroxyl in the system through the terminal active -NCO- group to form a stable urea bond structure, reduce the penetration and decomposition of water vapor into the EVA resin, and thus improve water resistance.
[0022] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description, claims and drawings.
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 This is a SEM image of the silane-modified nanomaterial provided in an embodiment of the present disclosure.
[0026] Figure 2 This is the infrared spectrum of the nanomaterial before and after modification provided in the embodiments of the present disclosure. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.
[0029] Herein, example embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as "at least one of..." modify the entire list of elements when following a list of elements, rather than modifying individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.
[0030] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.
[0031] In addition to the insufficient alkalinity and capture performance of inorganic nanomaterials themselves, directly adding alkaline nanomaterials or mixing through granulation machinery will also fail to bring out the synergistic effect of the components; at the same time, due to the high surface energy of nanomaterials, they are very easy to agglomerate. A high addition amount will cause low light transmittance of the film and high haze, thus limiting the amount of nano oxide added.
[0032] In addition, in addition to the acid value released by the aging and degradation of the film's own side chains in the component system, materials such as glass and backplane will also release free Na / K ions under the action of an external electric field. The ions penetrate the film and contaminate the passivation layer on the surface of the battery cell, causing the battery EL to deteriorate and turn black, and the PID to decay.
[0033] The defects existing in the above solutions are the results obtained by the inventor after practice and careful research. Therefore, the discovery process of the above problems and the solutions proposed by the present disclosure for the above problems below should be the contributions made by the inventor to the present disclosure during the disclosure process.
[0034] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0035] The embodiment of the present disclosure provides a method for preparing an acid-resistant photovoltaic adhesive film for an N-type battery, comprising the following steps: step S1, preparing a silane-modified nanomaterial, namely weighing a nano-oxide, acetone, alkaline silane and an acetic acid solution, heating and stirring to react and graft, and then centrifuging and heating and drying to obtain the silane-modified nanomaterial; step S2, blending the silane-modified nanomaterial with an ion capture agent, a carbodiimide anti-hydrolysis agent and an EVA resin in proportion, heating and extruding, and pelletizing after cooling to obtain a super acid-resistant masterbatch; step S3, mixing the super acid-resistant masterbatch and the EVA resin in proportion, adding an auxiliary agent, and then casting, embossing, cooling and winding in a screw extruder to obtain the acid-resistant photovoltaic adhesive film for the N-type battery.
[0036] In some embodiments, specifically, the step S1 specifically includes the following components in parts by weight: 5-10 parts of nano-oxide; 10-30 parts of acetone; 0.1-2 parts of alkaline silane; 0.1-0.5 parts of acetic acid; wherein the pH of the acetic acid is 3.
[0037] In some embodiments, specifically, the step S1 is heated and stirred for reaction, followed by centrifugation and heating and drying to obtain the silane-modified nanomaterial, specifically, the reaction is heated to 50°C and stirred for 3-5h, followed by centrifugation at 8000-12000r / min and then heated to 103°C for drying to obtain the silane-modified nanomaterial.
[0038] In some embodiments, specifically, the nano-oxide includes any one or more combinations of magnesium oxide, aluminum hydroxide, zirconium oxide, aluminum oxide, zinc oxide, zinc acetate, aluminum hydroxide, zinc hydroxide, hydrotalcite, zeolite, molecular sieve, calcium lactate and barium oxide.
[0039] In some embodiments, the basic silane includes 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminoethylaminopropyltrimethoxysilane, 3-(phenylamino)propyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylbis(trimethylsiloxy)methylsilane, N-(n-butyl)-r-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, A combination of any one or more of propyltrimethoxysilane, N-β-aminoethyl-γ-aminopropyltriethoxysilane, N-cyclohexyl-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, di(3-trimethoxysilylpropyl)amine, diethylenetriaminopropyltrimethoxysilane, monoaminosilane oligomer, bisaminosilane oligomer and N-n-butyl-3-aminopropyltrimethoxysilane.
[0040] In some embodiments, specifically, the ion capture agent includes any one or more combinations of anionic polyacrylamide, 18-crown ether-6 and polyether silane (commercially available Chenguang EO17).
[0041] In some embodiments, specifically, the carbodiimide anti-hydrolysis agent includes any one or more combinations of monomeric carbodiimide, polycarbodiimide and its derivative N,N'-dicyclohexylcarbodiimide.
[0042] In some embodiments, specifically, the step S2 specifically includes the following components in parts by weight: 80-96 parts of EVA resin; 2-10 parts of silane-modified nanomaterials; 1-5 parts of carbodiimide anti-hydrolysis agents; and 1-5 parts of ion capture agents.
[0043] In some embodiments, specifically, the auxiliary agent in step S3 includes an initiator, a co-crosslinking agent, a light stabilizer, an antioxidant and a silane coupling agent.
[0044] The disclosed embodiment also provides an acid-resistant photovoltaic adhesive film for N-type batteries, which is prepared by the method described above.
[0045] Example 1
[0046] Step S1: 5g of magnesium hydroxide and 30g of acetone are placed in a three-necked flask, 0.3g of acetic acid is added, the mixture is stirred and the temperature is raised to 50°C and refluxed for 1h, then 1g of 3-aminopropyltrimethoxysilane is added dropwise into the three-necked flask with a dropper, and the reaction is continued at 50°C for 2h. After the reaction is completed, the reaction solution is centrifuged at 8000-12000r / min, and the product after centrifugation is dried at 103°C to prepare a silane-modified nanomaterial.
[0047] Step S2: 90 parts of EVA resin, 5 parts of silane-modified nanomaterials, 2.5 parts of carbodiimide and 2.5 parts of anionic polyacrylamide are blended and granulated at 90-120° C. to obtain EVA acid-resistant masterbatch;
[0048] Step S3, blending 5 parts of EVA acid-resistant masterbatch and 90 parts of EVA base material, adding 0.05 parts of tert-butyl peroxy isopropyl carbonate, 0.06 parts of pentaerythritol triacrylate, 0.01 parts of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, 0.02 parts of 2,6-di-tert-butyl-p-methylphenol, and 0.03 parts of vinyl triethoxysilane, and then casting, embossing, cooling, and winding in a screw extruder to obtain an acid-resistant photovoltaic encapsulation film.
[0049] like Figure 1 As shown, the modified nanomaterial is in a highly dispersed state as a whole, and the particles have no obvious accumulation and agglomeration.
[0050] like Figure 2 As shown, the modified nanomaterial has a wavelength of 2400cm -1 and 3700cm -1 There is an obvious characteristic peak attributed to the NH bond near 1700cm -1 A stretching vibration peak attributed to CN (nitrile group) appeared nearby, proving that the amino group was successfully coated on the surface of the nanomaterial after surface treatment.
[0051] Some components in Example 1 were adjusted to obtain a high-transmittance and corrosion-resistant photovoltaic encapsulation film. The test results are shown in Table 1 below:
[0052] Table 1
[0053]
[0054]
[0055] Specifically, it can be seen from Comparative Example 1 that, without adding alkaline silane for modification, the acid value of the encapsulating film will be much higher than that of the embodiment, that is, the oxide in the conventional film has limited ability to capture free acid, which leads to a decrease in water barrier performance and an increase in the attenuation rate; it can be seen from Comparative Example 2 that, without adding an ion capture agent, although the acid value of the encapsulating film can be partially captured by the alkaline silane, long-term acid resistance cannot be achieved, so the increase in the attenuation rate is also very obvious.
[0056] Test method:
[0057] Light transmittance:
[0058] Take a piece of TPO film with a size of 30mm×30mm and two pieces of quartz glass with a size of 30mm×30mm (no embossing is required, and the transmittance is not less than 91.5%), put them into a vacuum press after overlapping the quartz glass / TPO film / quartz glass, and cross-link and cure them according to the product curing temperature and time (agreed by the supply and demand parties). After curing, take them out and put them into a dryer to cool to room temperature. The upper and lower surfaces of the cured sample should be flat and free of bubbles. Each group of samples should be no less than 3.
[0059] The samples were tested according to GB / T 2410-2008 Clause 7.2 Method B: Spectrophotometer method. The wavelength range of the spectrophotometer was set to 280nm~1100nm. At least 3 samples were tested in each group, and the results were averaged.
[0060] Acid value test:
[0061] Prepare 1 piece of ultra-clear embossed tempered glass not less than 200mm×200mm, 2 pieces of packaging film samples to be tested and 1 backplane.
[0062] After the above materials are stacked according to the structure of ultra-white embossed tempered glass / test film / test film / backplane, they are laminated as required, and the cross-linking degree of the encapsulation film after lamination should reach more than 80%. After the laminate is trimmed, the four sides are sealed with aluminum foil tape.
[0063] Within 12 hours after the aging is completed, take out the laminate in the test box and take a sample at least 50mm away from the edge of the laminate. Peel off the encapsulation film from the glass surface and remove the backplane. Cut the peeled encapsulation film into small pieces of about 5mm×5mm in size, weigh about 1g of the sample (record the actual mass M1) and add it to a conical flask containing a mixed solution (40ml xylene + 20ml ethanol), seal it with a glass stopper, and ultrasonicate for 15min. After the ultrasonication is completed, immerse the conical flask in cold water to cool it down.
[0064] After ultrasonic treatment, add about 0.3 g of bromothymol blue indicator to the conical flask containing the mixed solution of the film to be tested, and titrate with KOH ethanol solution of the calibrated concentration of the day until the end point color (light green) is consistent with the blank control sample, and keep it unchanged for at least 30 seconds. Record the actual volume of KOH ethanol solution consumed (V4).
[0065] Calculation of test acid value
[0066] The acid value of the sample is calculated according to formula (1) and expressed as micrograms of potassium hydroxide consumed per gram of sample, and the result is rounded to an integer.
[0067]
[0068] Where:
[0069] Cacid——the acid value of the sample, in micrograms per gram (ug / g);
[0070] V3——The volume of KOH ethanol solution consumed by the sample to be tested, in milliliters (mL);
[0071] V4——The volume of KOH ethanol solution consumed by the blank control sample (xylene + ethanol mixed solvent), in milliliters (mL);
[0072] C(KOH)——actual concentration of KOH ethanol solution, in moles per liter (mol / L);
[0073] 56.1 – constant, the molar mass of potassium hydroxide in grams per mole (g / mol);
[0074] M1——The mass of the sample, in grams (g).
[0075] PID192h:
[0076] The PID test and DH2000 aging test are tested with reference to the IEC61215 test standard. In the PID192 test, the cells and films are first prepared into photovoltaic modules according to the standard components, and the prepared photovoltaic modules are kept at a constant temperature in a room at 25°C for one day to ensure that the surface temperature of the modules is 25±1°C. The power tester is first calibrated with a standard plate, and then the initial power of the prepared modules is tested and recorded. The average value of the three tests is taken as the initial power generation power of the sample, which is the initial Pmax. Then the tested modules are placed in an aging box, the temperature is set to 85°C, the humidity is 85% RH, and a negative pressure of -1500V is applied. The aging time is 192h. After the aging is completed, the temperature is kept at a constant temperature in a room at 25°C for one day. The power after aging is tested, which is the power after aging, which is the Pmax after aging.
[0077] PID192h power attenuation = (initial Pmax - Pmax after aging) / initial Pmax * 100%
[0078] DH1000h aging:
[0079] The DH1000 aging test first prepares the solar cells and films into photovoltaic modules according to the standard components, and keeps the prepared photovoltaic modules in a room at a constant temperature of 25℃ for one day to ensure that the surface temperature of the modules is 25±1℃. First, calibrate the power tester with a standard plate, then test the initial power of the prepared modules and record it. The average value of the three tests is taken as the initial power generation power of the sample, which is the initial Pmax. Then place the tested modules in an aging box, set the temperature to 85℃, the humidity to 85%RH, and the aging time to 2000h. After the aging is completed, keep the room at a constant temperature of 25℃ for one day, and test the power after aging, which is the power after aging, which is the Pmax after aging.
[0080] DH1000 power attenuation = (initial Pmax - Pmax after aging) / initial Pmax * 100%
[0081] In summary, the acid-resistant photovoltaic adhesive film for N-type batteries and its preparation method adopt surface coating grafting technology for existing nanomaterials and introduce alkaline aminosilane coupling agents, which, on the one hand, improve the solid alkalinity of the nanomaterials, effectively improve the free acid capture ability, and increase the corrosion resistance of the film. At the same time, the surface free energy of the surface coating or powder is reduced, and the dispersion is better after granulation, which reduces the increase in haze caused by the introduction of nanomaterials and increases the light transmittance of the film.
[0082] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing an acid-resistant photovoltaic adhesive film for N-type batteries, characterized in that: The steps include: Step S1, preparing silane-modified nanomaterials, namely weighing nano-oxides, acetone, alkaline silane and acetic acid solution, heating and stirring for reaction grafting, then centrifuging and heating and drying to obtain silane-modified nanomaterials; Step S2, blending the silane-modified nanomaterial with the ion capture agent, the carbodiimide anti-hydrolysis agent and the EVA resin in proportion, heating and extruding, and pelletizing after cooling to obtain a super-acid-resistant masterbatch; Step S3, mixing the super acid-resistant masterbatch and the EVA resin in proportion, adding an auxiliary agent, and then casting, embossing, cooling, and winding in a screw extruder to obtain an acid-resistant photovoltaic adhesive film for N-type batteries.
2. The method for preparing the acid-resistant photovoltaic adhesive film for N-type battery according to claim 1, characterized in that: The step S1 specifically includes the following components in parts by mass: 5-10 parts of nano oxide; 10-30 parts of acetone; 0.1-2 parts of basic silane; 0.1-0.5 parts of acetic acid; in The pH of the acetic acid is 3.
3. The method for preparing the acid-resistant photovoltaic adhesive film for N-type battery according to claim 1, characterized in that: In step S1, the silane-modified nanomaterial is obtained by heating and stirring the reaction, then centrifuging and heating to dry the reaction mixture, specifically heating to 50° C. and stirring the reaction mixture for 3-5 hours, then centrifuging the reaction mixture at 8000-12000 r / min and then heating to 103° C. and drying the reaction mixture.
4. The method for preparing the acid-resistant photovoltaic adhesive film for N-type battery according to claim 1, characterized in that: The nano oxide comprises any one or more combinations of magnesium oxide, aluminum hydroxide, zirconium oxide, aluminum oxide, zinc oxide, zinc acetate, aluminum hydroxide, zinc hydroxide, hydrotalcite, zeolite, molecular sieve, calcium lactate and barium oxide.
5. The method for preparing the acid-resistant photovoltaic adhesive film for N-type battery according to claim 1, characterized in that: The basic silanes include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminoethylaminopropyltrimethoxysilane, 3-(phenylamino)propyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylbis(trimethylsiloxy)methylsilane, N-(n-butyl)-r-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxy A combination of any one or more of silane, N-β-aminoethyl-γ-aminopropyltriethoxysilane, N-cyclohexyl-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, di(3-trimethoxysilylpropyl)amine, diethylenetriaminopropyltrimethoxysilane, monoaminosilane oligomer, bisaminosilane oligomer and N-n-butyl-3-aminopropyltrimethoxysilane.
6. The method for preparing the acid-resistant photovoltaic adhesive film for N-type battery according to claim 1, characterized in that: The ion capture agent includes any one or more combinations of anionic polyacrylamide, 18-crown ether-6 and polyether silane.
7. The method for preparing the acid-resistant photovoltaic adhesive film for N-type battery according to claim 1, characterized in that: The carbodiimide anti-hydrolysis agent includes any one or more combinations of monomeric carbodiimide, polycarbodiimide and its derivative N,N'-dicyclohexylcarbodiimide.
8. The method for preparing the acid-resistant photovoltaic adhesive film for N-type battery according to claim 1, characterized in that: The step S2 specifically includes the following components by mass: 80-96 parts of EVA resin; 2-10 parts of silane-modified nanomaterial; 1-5 parts of carbodiimide anti-hydrolysis agent; 1-5 parts of ion capture agent.
9. The method for preparing the acid-resistant photovoltaic adhesive film for N-type battery according to claim 1, characterized in that: The auxiliary agents in step S3 include initiators, auxiliary cross-linking agents, light stabilizers, antioxidants and silane coupling agents.
10. An acid-resistant photovoltaic adhesive film for N-type batteries, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.
